Social environment mediates cancer progression in Drosophila - Erika H. Dawson (Nature Portfolio, 2018)
There is some evidence that social context can mediate the progression of cancers. Here, the authors show that Drosophila flies housed in social isolation experienced faster cancer tumor progression than flies in groups, and that flies select for social environments that minimize cancer risk.